Pollution Control Machine Using Artificial Intelligence And Machine Learning - Pandey, Anand; Manglik, Pragyadeep; Taluja, Punit (2019 International Conference on Computational Intelligence and Knowledge Economy (ICCIKE), 2019)
Research in pollution has been going from past several years and there have been many advancements in conserving and controlling the pollution and here motivated from the same and an important factor of humanity have led us to design a kind of Machine which will not only control the pollution but also convert the residual pollutants into a form that will be used to give the power supply to the machine. The machine is designed like a Traffic light pole with a similar kind of structure and there are many hardware devices put inside it like Electrostatic precipitator for synthesing the pollution and a converter cum inverter. Then the major role is played by some Information and Computing Technologies such as Artificial Intelligence, Computational Logic, Reinforcement Learning, Deep Neural Networks, IoT and Cloud Computing and these all are related to each other facilitating the overall efficient working of PCM.